Poster Presentation (Mazandaran University of Medical Sciences, 2015)
Invasive aspergillosis is one of the leading causes of morbidity and mortality among solid organ transplant recipients, especially in lung transplantations. Diagnosis of invasive aspergillosis is one of the current challenges due to nonspecific clinical symptoms and broad differential diagnosis. Definitive diagnosis usually requires invasive procedures, including bronchoscopy and CTguided biopsy